Improved Lead and Cadmium Adsorption from Wastewater Using Thermo-chemically Activated Bentonite: Equilibrium, Kinetics, and Thermodynamics - Madhumonti Saha; Pabitra Kumar Biswas; Jayanta Kumar Saha; Abhijit Sarkar; Sangeeta Lenka; M. Vassanda Coumar; Dinesh Kumar Yadav (Archives of Current Research International, 2025)
Aims: The effective treatment of wastewater contaminated with toxic metals such as lead (Pb) and cadmium (Cd) is vital for environmental sustainability and safe agricultural reuse as they are poisonous and may build up in the food chain, which can harm the ecosystem and cause health issues. Study Design: This study investigates the efficacy of thermo-chemically activated bentonite (Ac-Ben) compared to raw bentonite (Ben) for the removal of Pb(II) and Cd(II) from aqueous solutions using completely randomized design (CRD) in triplicates. Place and Duration of Study: Ac-Ben was synthesized and subsequent experiments were conducted at the Environmental Soil Science laboratory of ICAR-Indian Institute of Soil Science, Bhopal during 2023-2024. Methodology: Ac-Ben was synthesized by acid treatment of bentonite, and its enhanced physicochemical properties were confirmed via X-ray diffraction (XRD), scanning electron microscopy-cum-energy dispersive X-ray spectroscopy (SEM-EDX), Fourier transform infrared spectroscopy (FTIR), specific surface area analysis, and point of zero charge (PZC) measurements. Batch adsorption experiments evaluated the effect of contact time, pH, adsorbent dosage, temperature, and initial metal concentrations. Results: The adsorption process could be optimized with 60 min shaking time, solution pH = 5, 10 g L-1 adsorbent dose and 298 K reaction temperature. The pseudo-first-order kinetic model (R² ranges 0.996 to 0.999) and Langmuir isotherm best described the adsorption behavior, with Ac-Ben exhibiting higher maximum adsorption capacities (127.2 mg g-1 for Pb(II), 132.2 mg g-1 for Cd(II)) than Ben. Adsorption was spontaneous and exothermic, with reduced efficiency at elevated temperatures. Mechanistic analysis suggested that physisorption, electrostatic attraction, and ion exchange were the primary mechanisms. Ac-Ben maintained >85 % removal efficiency after three regeneration cycles, confirming its potential as a sustainable, efficient, and reusable adsorbent for heavy metal remediation from wastewater. Conclusion: Thermo-chemical activation markedly enhances bentonite’s affinity for Pb(II) and Cd (II). Owing to its abundance, low cost, and re-usability, Ac-Ben is a promising adsorbent for decentralized wastewater treatment, supporting SDG 6 on clean water.